Ability to Write Descriptive Texts in Elementary School Students - Putri Nur Intan Kumalasari; Cerianing Putri Pratiwi; Heny Kusuma Widyaningrum; Widyarini Susilo Putri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: Writing descriptive text aims to make the reader aware of what is written, stimulating the reader's feelings regarding what the writer is describing. The study aimed to determine the ability to write descriptive texts of grade V elementary school students. Method: The data sources used in this study are the results of writing student description texts as primary data sources and literature reviews on related topics as secondary data sources. This study uses a qualitative approach with a descriptive analysis method. The data collection technique in this study uses a documentation study with documentation, namely the results of writing description texts of class V students, which are then analyzed to obtain research results. Results: The results were obtained that students could write descriptive texts with sufficient categories, with an average score of 74%. Students get an average score of 66% on the punctuation writing accuracy indicator. Students get an average score of 72% with a sufficient category on the indicator of sentence structure accuracy. In the indicator of integration between sentences with a percentage of 74% with the sufficient category. Students can already use capital letters well, with an average percentage of 78%. Students could have a suitable category on the indicator of explanatory sentences according to the picture, with an average gain of 79%. Novelty: This study examines students' creativity level in writing descriptive texts based on images and error patterns in students' descriptive writing to know how to overcome existing problems.